Numerical simulation and field study on predicting wind-blown sand accumulation in sand mitigation measures of the Ganquan railway - Huang, Shiguang; Ma, Tao; Jiang, Fuqiang; Nie, Fei; Wang, Xuedong; Ma, Tiantian (Frontiers in Earth Science, 2024)
The accumulation of sand induced by wind poses a significant challenge to the safety and maintenance of railways in arid and desert regions. Accurate calculation and prediction of sand accumulation are crucial for ensuring continuous railway operation. This research is centered on the region significantly impacted by sand accumulation along the Ganquan Railway. Wind speed, wind direction, and sand carrying capacity data near this section were monitored. Using the collected wind speed, wind direction, and wind-sand flow density data, numerical simulations were conducted using the Computational Fluid Dynamics (CFD) method to predict the amount of sand accumulation within the sand mitigation measures of the Ganquan Railway. Monitoring results indicate that the dominant wind direction in spring and summer is due west, while in autumn and winter it is southwest, with an average wind speed of 12 m/s. A positive correlation was observed between wind-sand flow density and wind speed. The wind-sand flow density above 2 meters was nearly zero, indicating that the wind-sand flow structure is concentrated within 2 meters from the ground, with an average wind-sand flow density of 3.50×10 - 5 kg/m 3 . Through numerical simulation, the characteristics of the wind field and sand accumulation distribution within the calculation domain were determined. A relationship equation between sand accumulation mass and width over time was derived. Initially, the sand accumulation width increases uniformly and then stabilizes, while the sand accumulation mass rises uniformly to a plateau before increasing rapidly. From these findings, the optimal period for sand removal was identified as between 350 and 450 days after the sand mitigation measures are put into operation.